2020
DOI: 10.1177/0081246320912669
|View full text |Cite
|
Sign up to set email alerts
|

Participation in (non)violent protests and associated psychosocial factors: sociodemographic status, civic engagement, and perceptions of government’s performance

Abstract: A national representative sample of adults is used to assess whether socioeconomic circumstances, civic engagement, and perceptions about government performance are associated with participation in (non)violent protests. Blacks and those who report high levels of poverty and civic engagement are likely to participate in non-violent protests. Individuals who have not completed schooling, are members of an organisation, view government as highly corrupt, and rate government’s service delivery very unfavourably a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The global increase in protest is especially pronounced in South Africa (Duncan, 2016; Sikweyiya and Nkosi, 2017). Indeed, between 2015 and 2017, there were 340-375 protests recorded in the country (Swart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The global increase in protest is especially pronounced in South Africa (Duncan, 2016; Sikweyiya and Nkosi, 2017). Indeed, between 2015 and 2017, there were 340-375 protests recorded in the country (Swart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, protest research has shown that most protests occur in poor communities which lack basic infrastructure, service delivery, and overall development (Swart et al, 2020), with economic grievances cited as the main motivation for protest action (Sikweyiya and Nkosi, 2017). As the quality of life of most of the South African population has not improved since the formal end of apartheid in 1994, much scholarly attention has been paid to protester demographics, particularly race which “is often a proxy for income inequality” in the country (Swart et al, 2020: 481). In addition to race, however, age, sex, occupation, education, active civic engagement, and negative perceptions of government performance have also been assessed in the analysis of protest events (Swart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations